The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/rcm.5298
|View full text |Cite
|
Sign up to set email alerts
|

Using gas chromatography/isotope ratio mass spectrometry to determine the fractionation factor for H2 production by hydrogenases

Abstract: Hydrogenases catalyze the reversible formation of H(2), and they are key enzymes in the biological cycling of H(2). H isotopes have the potential to be a very useful tool in quantifying hydrogen ion trafficking in biological H(2) production processes, but there are several obstacles that have thus far limited the application of this tool. Here, we describe a new method that overcomes some of these barriers and is specifically designed to measure isotopic fractionation during enzyme-catalyzed H(2) evolution. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…All of these δD H 2 values were close to the theoretical δD H 2 value at the isotopic equilibrium between H 2 and H 2 O ( δD eq H 2 : see Additional file 2). Our observation is consistent with previous studies examining biologically produced H 2 that also revealed δD H 2 values close to the equilibrium (Walter et al 2012;Yang et al 2012). Note that the measured δD H 2 O -δD H 2 relationship showed increased deviation from the theoretically expected relationship in batches with higher δD H 2 O values (deviations of <26‰ for A1 and A2, <42‰ for A3 and A4, and <100‰ for A5 and A6).…”
Section: Results Of Thermophilic Coculture (Tc)supporting
confidence: 92%
See 1 more Smart Citation
“…All of these δD H 2 values were close to the theoretical δD H 2 value at the isotopic equilibrium between H 2 and H 2 O ( δD eq H 2 : see Additional file 2). Our observation is consistent with previous studies examining biologically produced H 2 that also revealed δD H 2 values close to the equilibrium (Walter et al 2012;Yang et al 2012). Note that the measured δD H 2 O -δD H 2 relationship showed increased deviation from the theoretically expected relationship in batches with higher δD H 2 O values (deviations of <26‰ for A1 and A2, <42‰ for A3 and A4, and <100‰ for A5 and A6).…”
Section: Results Of Thermophilic Coculture (Tc)supporting
confidence: 92%
“…In addition, the initial δD H 2 values were adjusted with respect to the theoretical δD H 2 values expected from the H 2 -H 2 O equilibrium, i.e., we prepared initial δD H 2 values that were higher (DH-rich), lower (D 2 O-rich), or almost identical to the equilibrated δD H 2 value at the incubation temperatures (Table 2). Moreover, we predicted that the initial δDH 2 value of the batch during methanogen growth would approach a δD H 2 value isotopically equilibrated with the medium H 2 O (Valentine et al 2004;Kawagucci et al 2014) because it is known that the functions of hydrogenases promote isotope exchange (Vignais 2005;Campbell et al 2009;Yang et al 2012;Walter et al 2012). Six batches for TP (C1-C6) and seven batches for MP (D1-D7) were examined (Table 2).…”
Section: General Notation Of Isotope Ratiosmentioning
confidence: 99%
“…An inorganic origin by chemodenitrification is likely, because soils surrounding nearby Don Juan Pond have been shown to produce N 2 O by this process with similar but variable δ 15 N and site preference values of −45.4‰ to −34.5‰ and −45.2‰ to 4.1‰, respectively (21). The δ 2 H of H 2 in the brine is similar to expected values for production from radiolysis and microbial hydrogenase activity (−692‰ and −793‰, respectively) based on the isotopic composition of the water (Table 1) and fractionation factors for these processes (22,23). Microbial H 2 consumption has been shown to catalyze nonproductive H 2 -water exchange and drive the δ 2 H of H 2 toward isotopic equilibrium with water on a monthly time scale (24).…”
Section: Resultssupporting
confidence: 74%
“…The deuterium enrichment in the emitted H 2 , compared to the value expected in isotopic equilibrium with water, could also be caused by different fractionations induced by different enzymes and/or a potentially enriched deuterium content of the substrate water available for H 2 production in Cabauw. H 2 is generated from the reduction of hydrogen ions (H + or D + ) in intracellular water (Yang et al, 2012). It was found that the isotopic composition of intracellular water can be different from that of extracellular water due to metabolic processing (Kreuzer-Martin et al, 2006).…”
Section: δD Of H 2 Emitted From the Soilmentioning
confidence: 99%